A Truthful Bilateral Multiunit Auction for Heterogeneous Cognitive Radio Networks - Jinzhao Su; Jianfei Wang; Wei Wu (International Journal of Distributed Sensor Networks)
Dynamic spectrum access technology has attracted much attention for its capability of improving spectrum efficiency. For attracting primary users to participate in secondary spectrum market, an auction was proposed as an alternative for spectrum trade. Existing auction schemes are either to be unilateral trade which only supports heterogeneous cognitive radio networks without guarantee of bid truthfulness, or to be truthful single-unit auction which only supports homogeneous channels. Few of them could comprehensively take all aspects of actual spectrum trade into consideration, such as spectrum allocation and reusability, channel diversity, and economic property. A truthful bilateral multiunit auction scheme which has characteristics of supporting heterogeneous networks (TBMAH) and polynomial complexity is proposed in this paper. We do experiments with both simulation and real networks, and the results show that TBMAH trades more spectrum resources than TRUST by 13.01% on average.